2008
DOI: 10.3177/jnsv.54.185
|View full text |Cite
|
Sign up to set email alerts
|

Gene Identification and Characterization of the Pyridoxine Degradative Enzyme .ALPHA.-(N-Acetylaminomethylene)succinic Acid Amidohydrolase from Mesorhizobium loti MAFF303099

Abstract: SummaryWe have found for the first time that a chromosomal gene, mlr6787, in Mesorhizobium loti encodes the pyridoxine degradative enzyme ␣ -( N -acetylaminomethylene)succinic acid (AAMS) amidohydrolase. The recombinant enzyme expressed in Escherichia coli cells was homogeneously purified and characterized. The enzyme consisted of two subunits each with a molecular mass of 34,000 Ϯ 1,000 Da, and exhibited Km and kcat values of 53.7 Ϯ 6 M and 307.3 Ϯ 12 min Ϫ 1 , respectively. The enzyme required no cofactor or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The activity of the active site mutants S106A, D130N, and S230C were assayed by measuring the decrease in the absorbance at 261 nm, the λ max for E -2AMS as previously described (7, 10). Each of these mutants was found to be completely inactive relative to the native enzyme, which retained an activity comparable to published results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The activity of the active site mutants S106A, D130N, and S230C were assayed by measuring the decrease in the absorbance at 261 nm, the λ max for E -2AMS as previously described (7, 10). Each of these mutants was found to be completely inactive relative to the native enzyme, which retained an activity comparable to published results.…”
Section: Resultsmentioning
confidence: 99%
“…This family has been structurally well characterized and includes esterases, lipases, epoxidases, alkane dehalogenases, carbon-carbon bond hydrolases, amidohydrolases, and thioesterases (33, 34). Previous analysis of the primary sequence for E -2AMS hydrolase using BLAST suggested that this enzyme was a member of the α/β hydrolase superfamily, despite a low sequence identity to this family of enzymes (10). A DALI search was performed using the structure of E -2AMS hydrolase and these results confirmed that E -2AMS hydrolase is a member of the α/β hydrolase family.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hydrolysis reaction has been well-characterized and the corresponding steady-state kinetic parameters have also been determined [13], [14]. Recently McCulloch and co-workers have proved that the hydrolase only utilizes E -2AMS rather than Z -2AMS as its substrate [13].…”
Section: Introductionmentioning
confidence: 99%